Superalloys 2000 (Ninth International Symposium) 2000
DOI: 10.7449/2000/superalloys_2000_273_282
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the High-Temperature Tensile Creep Strength of Monocrystalline Nickel-Base Superalloys by Pre-rafting in Compression

Abstract: In recent years, the development of Y.-hardened monocrystalline nickel-base superalloys focused on different aspects of alloy composition and microstructural refinement. In particular, the formation of so-called y/y'-raft structures, lying typically, in the case of a negative y/y'-lattice misfit 6, perpendicular to the stress axis during high-temperature tensile creep had attracted much attention. Unfortunately, this microstructural transformation leads in most cases to deteriorated creep properties. Earlier a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…in that region of a blade in which the combined action of thermal and mechanical loads is most severe (stress above ca. 150 MPa, temperature ≤ 950 C, compare [18]), the development of the raft structure leads to a deterioration of the mechanical properties of the alloy [9,19]. In this respect, it is interesting to investigate the effects of different alloying elements on the development of the γ/γ microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…in that region of a blade in which the combined action of thermal and mechanical loads is most severe (stress above ca. 150 MPa, temperature ≤ 950 C, compare [18]), the development of the raft structure leads to a deterioration of the mechanical properties of the alloy [9,19]. In this respect, it is interesting to investigate the effects of different alloying elements on the development of the γ/γ microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the TMF properties, Neuner et al [65] have shown that the pre-rafting of the microstructure seems to influence the fatigue life differently, depending on which TMF cycle is used. Further, Tetzlaff et al [66] showed that pre-rafting improves high-temperature creep properties.…”
Section: Tension Compressionmentioning
confidence: 99%
“…Creep deformation at high temperature leads to rafting of the γ/γ -microstructure and generally, the resistance to creep is improved due to this phenomenon because dislocations are prevented from climbing around the γ -particles and instead have to cut through the γ -particles [18]. More specifically, it has been shown that rafts parallel to the loading axis, obtained from pre-rafting, are beneficial to creep properties [66]. Rafting occurs rapidly; for example at 1150°C/100 MPa the rafting has been shown to be completed already after 10 h [51].…”
Section: Creepmentioning
confidence: 99%
“…According to Tetzlaff and Mughrabi,[24], and under the present low stress conditions, the P-type structure should be the most creep resistant due to its larger areas of vertical /' interfaces where the dislocation climb process is impeded most strongly. This lower creep strain rate compared to a cuboidal /' microstructure and to a N-type ' rafted one is maintained as long as fragmentation of the vertical plates is avoided.…”
Section: Effect Of the Prior Microstructure Degradationmentioning
confidence: 99%